Relationship between Neutrophil Lymphocyte Ratio and Lower Extremity Peripheral Artery Disease in Patients with Type 2 Diabetes Mellitus - Wibisana, Krishna Adi; Subekti, Imam; Antono, Dono; Nugroho, Pringgodigdo (Jurnal Penyakit Dalam Indonesia, 2018)
Introduction. Lower extremity peripheral artery disease (PAD) is one of diabetic macrovascular complication which has high rate of morbidity and mortality. Chronic inflammation has been known to have a role in the pathogenesis of PAD in diabetic patient. Recently, neutrophil lymphocyte ratio (NLR) has been used as a marker of chronic inflammation. This study aimed to determine the relationship between neutrophil lymphocyte ratio and lower extremity peripheral artery disease in type 2 diabetic patient in Cipto Mangunkusumo hospital. Methods. A cross sectional study was conducted on 249 patients with type 2 diabetes mellitus who underwent ankle brachial index (ABI) examination at Metabolic and Endocrinology Divison in Cipto Mangunkusumo Hospital between October 2015 – September 2016. The data were retrospectively collected from medical record. Lower extremity PAD was defined as having ABI value ≤ 0,9 by probe Doppler examination. Neutrophil lymphocyte ratio was categorized based on the median value and the relationship with lower extremity PAD were determined. Chi square test was used for bivariate analysis and logistic regression was used for multivariate analysis against confounding variables. Results. Lower extremity peripheral artery disease was found in 36 subject (14.5%). Median of NLR was 2.11. The median value of NLR was found higher in subjects with lower extremity PAD than without PAD (2.46 vs 2.04). There was an association between NLR value ≥ 2.11 and lower extremity PAD in type 2 diabetic patient (p=0.007; PR 2.46 and 95% CI 1.23 – 4.87). By using logistic regression, it was known that hypertension was the confounding variable. Conclusion. There is an association between neutrophil lymphocyte ratio and lower extremity peripheral artery disease in type 2 diabetic patients in Cipto Mangunkusumo Hospital.